In vitro antidiabetic of cemumar (Micromelum pubescens), tebengau (Ehretia laevis) and kedondong (Spondias dulcis) leaves extract - Nuridayu Jantan (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
In vitro method is widely used to determine the antidiabetic activities in herbal plants. The method does not involved human body or animal as the model in the experiment. In this project, three types of plant are selected because they are traditionally used in the treatment of diabetic disease. In order to study their antidiabetic activities, the experiment was conducted using an in vitro method which mimicked the diffusion mechanism of glucose from the intestinal membrane through the blood stream. The datafrom the experiment are manipulated using Stat-Ease software, which is one of the design of experiment method to prove whether the model is significant. The software contains analysis of variance (ANOVA) to analyze the data according to its curvature, standard deviation and lack of fit. Result of the experiment has observed that Kedondong (Spondias dulcis) has comparatively higher antidiabetic activity where as the Cemumar (Micromelum pubescens) shows the negative deviation and represented as the lowest antidiabetic from the others. Therefore, it is interesting to study the influenced of the extract at different concentration.